1983
DOI: 10.1126/science.6682243
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Chorionic Gonadotropin: Synthesis by the Human Fetus

Abstract: The kidney, and to a slight extent the liver, of human fetuses were found to synthesize and secrete the alpha subunit common to glycoprotein hormones. Fetal lung and muscle did not synthesize this protein. Since fetal kidney and liver were previously found to synthesize beta chorionic gonadotropin, their ability to synthesize bioactive chorionic gonadotropin was also determined. The newly synthesized hormone bound to mouse Leydig cells and elicited a biological response: namely, the synthesis of testosterone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 11 publications
(11 reference statements)
2
11
1
Order By: Relevance
“…Our results indicated that human fetal kidney and, to a slight extent, fetal liver could synthesize and secrete a protein that was immunologically and electrophoretically identical to /?hCG (6). Recently, we have obtained similar results for the a-subunit common to hCG and other glycoprotein hormones (7). We have also demonstrated that the hCG present in these tissues is biologically active (5,7).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Our results indicated that human fetal kidney and, to a slight extent, fetal liver could synthesize and secrete a protein that was immunologically and electrophoretically identical to /?hCG (6). Recently, we have obtained similar results for the a-subunit common to hCG and other glycoprotein hormones (7). We have also demonstrated that the hCG present in these tissues is biologically active (5,7).…”
supporting
confidence: 85%
“…Recently, we have obtained similar results for the a-subunit common to hCG and other glycoprotein hormones (7). We have also demonstrated that the hCG present in these tissues is biologically active (5,7). In continuation of these Received February 25,1983.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Böckers et al (1994) detected FSH receptor mRNA in testicular tissue. By contrast, there are a few reports that the testicular tissue of the marmoset monkey and the kidney or liver tissue of the human fetus can synthesize in vitro FSH and human chorionic gonadotropin molecules, respectively (McGregor et al 1981(McGregor et al , 1983Garde et al 1991). It is therefore difficult to determine if the presence of LH-like substance in the cytoplasm of the epithelial cells in our study could be due to receptorbound or endogenous synthesized molecules in the lung and stomach.…”
Section: Discussioncontrasting
confidence: 63%
“…This maternal placental supply of CG peaks at the beginning of the 3rd month of gestation, declines slightly for 4-5 weeks, then begins a pronounced decline early in the 4th month of gestation. As the maternal placental levels of CG subside in the 3rd month, the fetus itself begins to produce the hormone (McGregor, Kuhn, & Jaffe, 1983). In addition, during the 3rd month of gestation, fetal production of LH becomes significant (Reiter & Grumbach, 1982).…”
Section: Genital Dimensionmentioning
confidence: 99%